High-Throughput Screening Assay Identifies Small Molecules Capable of Modulating the BMP-2 and TGF-β1 Signaling Pathway. (January 2017) - Ghebes, Corina-Adriana; van Lente, Jéré; Post, Janine Nicole; Saris, Daniel B. F.; Fernandes, Hugo
Modulating the bone morphogenetic protein 2 (BMP-2) and transforming growth factor–β1 (TGF-β1) signaling pathways is essential during tendon/ligament (T/L) healing. Unfortunately, growth factor delivery in situ is far from trivial and, in many cases, the necessary growth factors are not approved for clinical use. Here we used a BMP-2 and a TGF-β1 reporter cell line to screen a library of 1280 Food and Drug Administration–approved small molecules and identify modulators of both signaling pathways. We identified four compounds capable of modulating BMP and TGF signaling on primary human tendon–derived cells (huTCs) and describe their effects on proliferation and differentiation of these cells.